The Effect of Work Stress on Employee Performance - Karim, Kurniati (Asean International Journal of Business, 2022)
The purpose of this research is to determine the effect of work stress during the Covid19 pandemic on employee performance. This research uses a qualitative descriptive method. Where to process the author's data using SPSS version 23. This research was conducted onPT Pan Baruna Pekanbaru Pekanbaru Riau Indonesia. The sample in this study were employees of PT. Pan Baruna was limited by the administration division and the sales division, which amounted to 87 people. Sample selection using purposive sampling method. In collecting data, the author uses primary data sources with questionnaires as a tool.Based on table 5.47, it can be seen that the simple linear regression equation formed is Y = 93.147 + (-0.822X). From these equations it can be explained that if the work stress variable increases by 1%, then the work performance of employees at PT. Pan Baruna Pekanbaru Branch decreased by 0.822. This shows that the work stress variable contributes negatively to employee performance, so that the work stress level of PT. Pan Baruna Pekanbaru Branch, the